Psychometric properties of the arabic version of occupational value with pre-defined ítems - Mona Eklund; Lisa Ekstam; Mariam Hassan; Pablo Bellosta-López (Scandinavian Journal of Occupational Therapy)
Background Perceived occupational value is closely linked with well-being and there is need worldwide for assessment tools that target this phenomenon. The Occupational Value with pre-defined items (OVal-pd), measuring three dimensions of occupational value; concrete, socio-symbolic and self-rewarding, was designed for that purpose.Aim To pilot an Arabic version of OVal-pd and evaluate its psychometric properties in terms of content validity, factor structure, homogeneity, construct validity, test-retest stability, floor and ceiling effects, and measurement error.Methods Snowball sampling was used to recruit Arabic-speaking persons living in Sweden (n = 55). They completed the OVal-pd and questionnaires addressing background factors, content validity and feasibility. Confirmatory factor analysis, Spearman’s rank correlation, Cronbach’s α, intraclass correlation coefficients, and minimum detectable change were calculated.Results A 22-item version of the Arabic OVal-pd was found to have acceptable content validity and feasibility and the proposed three occupational value dimensions were confirmed. Good properties in terms of construct validity, internal consistency and test-retest stability were also established. No floor or ceiling effects were observed.Conclusion The Arabic OVal-pd showed good validity and reliability on various psychometric aspects.Significance In today’s multicultural societies, the Arabic OVal-pd can be an important tool for occupational therapists working with Arabic-speaking clients.